Ant Community Structure (Hymenoptera: Formicidae) in Two Neighborhoods with Different Urban Profiles in the City of São Paulo, Brazil - Alcione Piva; Ana Eugênia de Carvalho Campos (Psyche: A Journal of Entomology)
Some ant species are highly abundant in cities, may form huge unicolonial populations with thousands of individuals able to displace native fauna, and impoverish ecological relationships in urban environments. In this work, we study the ant community in two neighborhoods with different urban profiles, one recently populated and another from the 1900s in the city of São Paulo, Brazil. Two hundred and ninety houses were sampled with baits for ant collections. Results show that the recent urbanized neighborhood with greater disturbance favors opportunistic and dominant species to colonize it, like Tapinoma melanocephalum. We also made a temporal analysis in the ancient neighborhood, collecting ants after ten years from a first survey. T. melanocephalum has a broader range than ten years ago, displaced other ant species, but confronts with Pheidole megacephala that was not found in the recent urbanized neighborhood.